2019
DOI: 10.1016/j.ijdevneu.2019.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI study of infant regional brain size following surgery for long‐gap esophageal atresia requiring prolonged critical care

Abstract: Introduction Little is known regarding the impact of concurrent critical illness and thoracic noncardiac perioperative critical care on postnatal brain development. Previously, we reported smaller total brain volumes in both critically ill full‐term and premature patients following complex perioperative critical care for long‐gap esophageal atresia (LGEA). Our current report assessed trends in regional brain sizes during infancy, and probed for any group differences. Methods Full‐term (n = 13) and preterm (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(45 citation statements)
references
References 75 publications
7
37
1
Order By: Relevance
“…We also report decreased normalized CC volumes in both full-term and premature patients scanned after complex perioperative LGEA treatment. This interesting finding is in contrast to our recent T2-weighted MRI study report 10 , which showed global decrease of gross brain, forebrain, and deep gray matter (viz. thalamus and basal ganglia) volumes.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We also report decreased normalized CC volumes in both full-term and premature patients scanned after complex perioperative LGEA treatment. This interesting finding is in contrast to our recent T2-weighted MRI study report 10 , which showed global decrease of gross brain, forebrain, and deep gray matter (viz. thalamus and basal ganglia) volumes.…”
Section: Discussioncontrasting
confidence: 99%
“…Likewise, normalized CC surface areas (% intracranial space surface area; graph C) differed among the groups with significantly smaller normative CC surface area found only between full-term patients and controls (p = 0.004). (2020) 10:6408 | https://doi.org/10.1038/s41598-020-63212-3 www.nature.com/scientificreports www.nature.com/scientificreports/ possibly implicate subtle cortical neuronal and/or astrocytic vulnerability in the setting of LGEA treatment, not previously seen by analysis of gross forebrain structure as a whole 10 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations